Effect of manipulative treatment in patients with mechanical neck pain: a systematic review - Teles, Jossandra Cássia de Maria Alves; Oliveira, Daniel Nunes de; Mota, Antônia Vitória Silva; Gomes, Patrícia Xavier Lima; Santos-Júnior, Francisco Fleury Uchôa (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The neck pain especially of mechanical origin (related to the joints of the spine) interfere in health and quality of life of individual widely affecting the population. Objective: Analyze through a systematic review the effectiveness of manipulation as a therapeutic tool in neck pain. Method: The search was performed using the following databases: Scientific Electronic Library Online (SCIELO), Virtual Health Library (BIREME), PubMed (MEDLINE) and Google Scholar with the descriptors “Cervical manipulation”, as well as associated with the word “joint”, in the last 14 years (2001 to 2015). The search resulted in 446 articles of which 49 were selected for reading the full text, but only 10 articles contemplated the methodological criteria. There were included studies that approach about the neck pain, using manipulation associated with physiotherapy techniques. Reviews, master and doctoral thesis and Completion of Course Work were excluded, as well as studies involving animals. Results: The articles included in this study were submitted to methodological quality analysis of the PEDro scale, in which all items have average higher than or equal to six. The sample size ranges from 6 to 96 subjects with age between 18 and 65 years old. Regarding the gender of patients the prevalence was 35.71% for males and 64.28% for females, being this one predominant in the studies included in the research. The majority of the evaluated articles proved to be favorable to cervical manipulation with improvement of pain in 48.9% of patients in primary care and about 75% decreased in 6 months, as well as improvement of functional limitation. Conclusions: The cervical manipulation proved to be an important and effective technique in the treatment of mechanical neck pain, because it can minimize the painful condition and restore range of motion.